2012
DOI: 10.1017/s0025100312000102
|View full text |Cite
|
Sign up to set email alerts
|

Czech spoken in Bohemia and Moravia

Abstract: As a western Slavic language of the Indo-European family, Czech is closest to Slovak and Polish. It is spoken as a native language by nearly 10 million people in the Czech Republic (Czech Statistical Office n.d.). About two million people living abroad, mostly in the USA, Canada, Austria, Germany, Slovakia, and the UK, claim Czech heritage (Ministry of Foreign Affairs of the Czech Republic 2009). However, it is not known how many of them are native speakers of Czech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…The results showed that the high front vowel pair is reliably distinguished by F1: the long /iː/ has a smaller F1 than the short /ɪ/, by 2 ERB, a difference which by far exceeds the just noticeable difference for formants (which is 0.2 ERB for [ɪ]-like vowels, Kewley-Port, 1995).The significant lowering of the short /ɪ/ in the vowel space is further documented by this vowel being, in terms of F1, four times closer to the short mid back /o/ than the long /i:/ is to the long mid /o:/. This F1 distinction between /ɪ/ and /iː/ is in line with previous acoustic measurements of vowels from read speech (Skarnitzl & Volín, 2012;Šimáčková et al, 2012;Paillereau, 2016) and matches the impressionistic observations of spontaneous speech from the 20th century (Frinta, 1909(Frinta, , 1924Beneš, 1943;Chlumský, 1928;Hála, 1955; note that Hála, 1941Hála, , 1962 noticed an openess not only of the short but also of the long front high vowel).…”
Section: Acoustic Characteristics Of Czech Monophthongssupporting
confidence: 89%
See 3 more Smart Citations
“…The results showed that the high front vowel pair is reliably distinguished by F1: the long /iː/ has a smaller F1 than the short /ɪ/, by 2 ERB, a difference which by far exceeds the just noticeable difference for formants (which is 0.2 ERB for [ɪ]-like vowels, Kewley-Port, 1995).The significant lowering of the short /ɪ/ in the vowel space is further documented by this vowel being, in terms of F1, four times closer to the short mid back /o/ than the long /i:/ is to the long mid /o:/. This F1 distinction between /ɪ/ and /iː/ is in line with previous acoustic measurements of vowels from read speech (Skarnitzl & Volín, 2012;Šimáčková et al, 2012;Paillereau, 2016) and matches the impressionistic observations of spontaneous speech from the 20th century (Frinta, 1909(Frinta, , 1924Beneš, 1943;Chlumský, 1928;Hála, 1955; note that Hála, 1941Hála, , 1962 noticed an openess not only of the short but also of the long front high vowel).…”
Section: Acoustic Characteristics Of Czech Monophthongssupporting
confidence: 89%
“…Frinta, 1909;Hála, 1962) who, however, did not consider it significant enough to be captured in the transcription (Frinta, 1925). The spectral differentiation of /iː/-/ɪ/ has been objectively confirmed by a number of recent acoustic measurements (Skarnitzl & Volín, 2012;Šimáčková et al, 2012;Paillereau, 2016;Chládková et al, 2019). Spectral differentiation of a phonological length contrast, comparable to that attested in /iː/-/ɪ/, has not (yet) been found for the high back vowels, although some note a potential trend in that respect (either explicitly as Skarnitzl & Volín, 2012, or implicitly by transcribing the vowels as /uː/ /ʊ/ in Duběda, 2005).…”
Section: The Czech Vowel Systemmentioning
confidence: 63%
See 2 more Smart Citations
“…Czech is a vowel-length language contrasting the monophthongs /iː, ɪ, ɛː, ɛ, aː, a, oː, o, uː, u/ (Šimáčková, Podlipský & Chládková 2012). Native Czechs are highly sensitive to vowel duration in speech even when listening to non-Czech vowels (Chládková, Escudero & Lipski 2013).…”
Section: High Back Vowels In Czech and Englishmentioning
confidence: 99%